Institutional constraints on the executive, investment, and elections. - Canes‐Wrone, Brandice; Ponce de León, Christian; Thieme, Sebastian (Presidential Studies Quarterly, 2023)
In recent years, a variety of countries worldwide have experienced an increase in executive power. Long‐standing concerns about this concentration include reduced property rights protection. Particularly for developing democracies, scholars theorize that a lack of institutional constraints on the executive may impede long‐term investment. Analyzing this question empirically has proven difficult, however, because economic activity can affect political institutions and behavior. This article, which analyzes four decades of data from 57 developing democracies, addresses the identification challenges by leveraging elections as a source of exogenous turnover and by accounting for the potential endogeneity of executive institutions. Consistent with the argument that institutional constraints reassure investors, the results suggest that as constraints on the executive increase, investment is less affected by prospective electoral turnover. Moreover, the results are stronger for presidential and semi‐presidential systems with fixed elections, where the chief executive's term cannot be ended early by elections or the legislature, than for parliamentary systems.